Overview of the Mechanism of Action of Gentiana Scabra in the Treatment of Rheumatoid Arthritis - Miao, Hongli; Zhang, Yanchun (Journal of Contemporary Medical Practice, 2024)
Objective: To provide a comprehensive review of the research on the analgesic, anti-inflammatory, anti-swelling and analgesic effects of Radix Gentiana Macrophylla. Methods: Gentiana macrocephala has an analgesic effect in modern research, commonly used in various rheumatism and paralysis, numbness, contracture and soreness of the muscles and bones and other diseases of the pain treatment, can be extracted from the sterol glycoside salts and other medicinal components, its anti-inflammatory and analgesic and treatment of acute arthritis episodes of the clinical effect of the performance of the particularly unique and significant. The results can make the joint swelling, pain and other symptoms can be reduced, and the risk of reoccurrence can also be reduced after the introduction of the drug. Conclusion: In the treatment of rheumatoid arthritis, Gentiana Macrophyllae alone and in combination can improve joint symptoms such as stiffness, swelling, pain, distension and deformity as well as other systemic symptoms of rheumatoid arthritis.